A general method to combine environmental and life-safety consequences of Arctic ship accidents. (October 2022) - Browne, Thomas; Taylor, Rocky; Veitch, Brian; Helle, Inari; Parviainen, Tuuli; Khan, Faisal; Smith, Doug
Highlights: A general method to combine multiple consequences posed by Arctic ship accidents. Ecological and socio-economic consequences of an oil spill and life-safety consequences of an evacuation in Arctic waters are considered. Consequence types are monetized and summed to quantify a total consequence cost. A framework to qualitatively rate total consequence severity is proposed. Total consequence severity for different ship types and regions in the Canadian Arctic are evaluated. Abstract: Risk aggregation is the process of combining multiple individual risks to develop a better understanding of the overall risk on a system. Different risks can have different consequences and different units of measure. This study contributes to the process of risk aggregation by presenting a general method to combine multiple consequences posed by an Arctic ship accident. The method considers ecological and socio-economic consequences of a potential oil spill, and life-safety consequences of a potential ship evacuation. Existing models for each consequence type are adopted. Individual consequence types are monetized and combined to quantify total consequence cost for a given accident scenario. A framework is proposed to assign a qualitative rating for total consequence severity. The qualitative scales of the framework are established using the quantitative method. Total consequence severity is evaluated for different ship types and regions in the Canadian Arctic. Results indicate that Arctic ship accidents involving oil tankers in environmentally sensitive regions and cruise ships in regions associated with long response times are worst-case scenarios, with similar total consequence severity levels. Implications for safe Arctic shipping are that on the basis of total consequence severity, mitigating the potential consequence severity of Arctic cruise operations is of near equal priority to that of Arctic tanker operations. Evaluating total consequence severity of potential Arctic ship accidents provides decision-makers and risk analysts with a data-driven tool to integrate multidisciplinary knowledge for the assessment, management, and communication of Arctic shipping risks.